2021
DOI: 10.7586/jkbns.2021.23.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Clary Sage Oil before Chemotherapy Alleviates Anxiety and Stress without Changing Blood Pressure: A Randomized Controlled Trial

Abstract: Purpose:The purpose of this study was to evaluate the effects of inhaled clary sage (Salvia sclarea L.) oil or linalyl acetate on patients' anxiety and stress levels before undergoing chemotherapy. Methods: Forty-five eligible participants were randomly assigned to inhale clary sage oil, or linalyl acetate, each at concentrations of 5% vol/vol in almond oil or pure almond oil (control). State-trait anxiety inventory (STAI), Stress rating scale, anxiety-visual analog scale (Anxiety-VAS), stress-visual analog sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A study of rats found that inhalation of lavender oil ameliorated anxiety-like and depression-like behaviors induced by corticosterone injection [ 47 ]. A clinical study showed that inhalation of linalyl acetate reduced the levels of anxiety and stress in cancer patients prior to chemotherapy [ 48 ]. The present finding that lavender oil reduced affective pain in patients with postherpetic neuralgia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A study of rats found that inhalation of lavender oil ameliorated anxiety-like and depression-like behaviors induced by corticosterone injection [ 47 ]. A clinical study showed that inhalation of linalyl acetate reduced the levels of anxiety and stress in cancer patients prior to chemotherapy [ 48 ]. The present finding that lavender oil reduced affective pain in patients with postherpetic neuralgia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LA has been shown to have positive effects on mood. Inhalation of LA by cancer patients prior to chemotherapy decreased the anxiety-visual analogue scale (VAS) and the stress-VAS scores in cancer patients, suggesting that LA has anti-anxiety and anti-stress effects (Kim et al, 2021). Inhalation of lavender, petitgrain, or bergamot essential oil containing large amounts of LA was found to reduce the Anger-Hostility and the Tension-Anxiety scores in pregnant women (Igarashi, 2013).…”
Section: Effects Of La On Mood and Cognitionmentioning
confidence: 99%
“…The sample size was calculated using the G-Power program (version 3.1) to compare means in two independent groups (21). Based on a statistical power of 0.80, an effect size of 0.80, and a significance level of 0.05, the required number of participants was 26 for each group (marjoram and control).…”
Section: Setting and Participantsmentioning
confidence: 99%